Tail risk spillover, transmission path and evolution mechanism of new energy vehicle companies in China: An industry chain perspective - Zimo Feng; Haoyi Hou; Jing Deng (Sustainable Futures)
China’s new energy vehicle industry chain has strong advantages but faces risks such as rapid technological changes, global supply chain dependencies, policy volatility, and market dynamics. Properly identifying and managing these risks is essential for the industry’s sustainable development. This study addresses three main questions: how does the total risk connectedness of the NEV industry chain evolve, how do risks spread within the chain, and which companies significantly contribute to overall risk? Using the tail-event driven network risk (TENET) method and the planar maximally filtered graph (PMFG), this study reveals that risk spillovers significantly increase during some global events. Moreover, the upstream and midstream sectors are key sources of risk, with midstream companies mainly acting as absorbers of risk. The main risk transmission follows an ”upstream–middle–downstream” pathway, although this can reverse in extreme cases. Companies involved in lithium mining, diaphragm production, and battery manufacturing exhibit high systemic risk contributions, marking them as critical nodes in the supply chain. The paper concludes with targeted policy recommendations to support the NEV industry’s sustainable growth and ensure the safety of its supply chain.